INFLUENCE CONSTRUCTION OF THE ROLLER ON THE POWER OF THE DRIVE SYSTEM OF THE BELT CONVEYOR - Tadeusz OPASIAK; Damian GĄSKA; Grzegorz PERUŃ; Bogusław ŁAZARZ (Scientific Journal of Silesian University of Technology. Series Transport)
The paper presents a study of new design of rollers. The study focused on the measurement of static and dynamic resistance of rotating rollers and the impact of new construction on the power consumption of the belt conveyor. Rollers have been modified through the use of class C4 bearing seals and labyrinth seal U4Exp 62/65 with a cover 2LU4 of runner construction. Measurements of static and dynamic resistance of rotating rollers were made on a universal rollers stand and power measurements were carried out on a belt conveyor power supply system Gwarek 1200 No. TW in mine KWK Mysłowice–Wesoła.